Translating Research Findings Into Practice: Example of Treatment Services for Adolescents in Managed Care - Sterling, Stacy (Alcohol Res Health, 2006)
An important question in the alcoholism treatment field is how research findings can be translated into real-world clinical practice. Researchers have developed a new research–practice integration (RPI) model that can both drive the formulation of studies and new research questions and promote improvements in treatment quality. The hallmark of this model is a collaborative relationship between the key stakeholders in both alcohol and other drug (AOD) treatment and research, including health plan administrators and clinicians, treatment program administrators, psychiatry and primary care departments, patients and their families, purchasers, and researchers. The issue of technology transfer is especially relevant in the realm of adolescent AOD treatment. The implementation and feasibility of the RPI model are illustrated by a case study of a managed health care plan’s treatment services for adolescents with AOD dependence. In this setting, key research findings are being used to shape the plan’s adolescent health services.